Simplify: #{(6^6)^4 -: (6^7)^0 xx[(6^2)^3]^2}^2 -: {[(6^3)^5xx(6^2)^3]^3 : [(6^3)^3]^4}^2#?

Answer 1

#6^18#

#{(6^6)^4-:(6^7)^0xx[(6^2)^3]^2}^2-:{[(6^3)^5xx(6^2)^3]^3-:[(6^3)^3]^4}^2#
= #{6^(24)-:6^0xx6^(12)}^2-:{[6^(15)xx6^6]^3-:[6^9]^4}^2#
= #{6^(24-0+12)}^2-:{[6^(15+6)]^3-:6^36}^2#
= #{6^(36)}^2-:{[6^(21)]^3-:6^36}^2#
= #6^(72)-:{6^(63)-:6^36}^2#
= #6^(72)-:{6^(63-36)}^2#
= #6^(72)-:{6^(27)}^2#
= #6^(72)-:6^(54)#
= #6^(72-54)#
= #6^18#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

To simplify the expression, we'll start by evaluating the exponents within each set of parentheses:

(6^6)^4 = 6^(6*4) = 6^24

(6^7)^0 = 6^(7*0) = 6^0 = 1

(6^2)^3 = 6^(2*3) = 6^6

[(6^2)^3]^2 = (6^6)^2 = 6^(6*2) = 6^12

Now, let's substitute these values back into the original expression:

{6^24 ÷ 1 ×× 6^12}^2 ÷ {[(6^3)^5 ×× 6^6]^3 ÷ [(6^3)^3]^4}^2

This simplifies to:

{6^24 ×× 6^12}^2 ÷ {[6^(35) ×× 6^6]^3 ÷ [6^(33)]^4}^2

{6^36}^2 ÷ {[6^15 ×× 6^6]^3 ÷ 6^12}^2

Now, we'll simplify the expressions within the brackets:

{6^72} ÷ {[6^21]^3 ÷ 6^12}^2

Now, we'll simplify the expression within the square brackets:

{6^72} ÷ {[6^(21*3) ÷ 6^12]}^2

{6^72} ÷ {[6^63 ÷ 6^12]}^2

{6^72} ÷ {6^(63-12)}^2

{6^72} ÷ 6^51^2

{6^72} ÷ 6^102

Now, subtract the exponents:

6^(72-102) = 6^-30

Thus, the simplified expression is 1/(6^30).

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 3

To simplify the expression, follow the order of operations (PEMDAS/BODMAS) which stands for Parentheses/Brackets, Exponents/Orders, Multiplication and Division (from left to right), and Addition and Subtraction (from left to right).

First, simplify the expressions within the parentheses/brackets and exponents:

  1. ((6^6)^4 = 6^{6 \times 4} = 6^{24})
  2. ((6^7)^0 = 1) (Any non-zero number raised to the power of 0 equals 1)
  3. ((6^2)^3 = 6^{2 \times 3} = 6^6)
  4. (6^6 = 46656)
  5. (6^3 = 216)

Now, substitute these values back into the original expression:

[\frac{{46656^2}}{{(1 \times [6^6]^2)}} \div \frac{{(216^5 \times 46656)}}{{(46656^3 \times 216^3)^2}}]

Now, perform the operations within the brackets:

  1. ([6^6]^2 = 46656)
  2. (216^5 = 2,176,782,336)
  3. (46656^3 = 89,916,082,944)
  4. (216^3 = 10,077,696)

Now, substitute these values back into the expression:

[\frac{{46656^2}}{{(1 \times 46656)}} \div \frac{{(2,176,782,336 \times 46656)}}{{(89,916,082,944 \times 10,077,696)^2}}]

Now, perform the remaining operations:

  1. (46656^2 = 2,176,782,336)
  2. (1 \times 46656 = 46656)
  3. (89,916,082,944 \times 10,077,696 = 906,573,791,866,017,024)
  4. ((906,573,791,866,017,024)^2 = 82,045,248)

Now, perform the division:

[\frac{{2,176,782,336}}{{46656}} \div \frac{{2,176,782,336 \times 46656}}{{82,045,248}}]

Now, perform the division:

[\frac{{46656}}{{46656}} \div \frac{{2,176,782,336 \times 46656}}{{82,045,248}}]

[\frac{{1}}{{1}} \div \frac{{101,551,978,898,622,976}}{{82,045,248}}]

[\frac{{82,045,248}}{{101,551,978,898,622,976}}]

Therefore, the simplified expression is approximately (8.0813565 \times 10^{-13}).

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7